Car health monitoring system using Arduino - Mohd Faizal, Zulkeffali (2019)
Car has become main daily transportations in Malaysia. Regular car maintenance is one of the key procedures to sustain its performance. In addition, good maintenance able to reduce the risk of car problems which might affect drivers and passengers safety while traveling and reduce the expenses for repairing. Good car care can rewards the owner in term of time, money and safety. In the interval duration, it is the car owner responsibility to monitor the car condition. The problem of machine will normally start with small indication, sound or irregular events. In monitoring such indications, notification system is known as one of the good methods. Nowadays, smartphones turn out to be essentials in assisting human life. Therefore, this project aim to develop an android based mobile application to monitor the car condition where it will notify the owner about the excessive heating of car engine. The methodology that has been implemented in this project is Rapid Application Development (RAD) that have four phases including requirements planning, user design, construction and cutover phases. This project is developed based on a proposed model for effective monitoring of motor heating. The system implemented an Arduino and React Native for mobile application which used to separate different parameters; i.e. motor heating to ensure the driving is protected and always cautious. The collected temperatures data which are sent through internet will be received by mechanic and car owner by using the application. The hardware unit involves Arduino, Bluetooth module, LCD (Liquid Crystal Display), android based smartphone, temperature sensor and particular parameter checking sensors module. The application is tested based on User Acceptance Test with the client by test the bluetooth connection between Arduino and android smartphone , view the real time data result stored in database by display all of the data retrieve on smartphone. In conclusion, it is hope this project can contribute to my client and other people to improve their lifestyle in using new technology.